Ethnicity-specific prevalences of refractive errors vary in Asian children in neighbouring Malaysia and Singapore. Issue 10 (29th June 2006) - Saw, S-M; Goh, P-P; Cheng, A; Shankar, A; Tan, D T H; Ellwein, L B
Abstract : Aim: To compare the prevalences of refractive errors in Malay, Chinese and Indian children in Malaysia and Singapore. Methods: Children aged 7–9 years from three schools in the Singapore Cohort study of the Risk factors for Myopia (n = 1962) and similarly aged children from a random cluster sample in the metropolitan Kuala Lumpur area in the Malaysia Refractive Error Study in Children (n = 1752) were compared. Cycloplegic autorefraction was conducted in both countries. Results: The prevalence of myopia (spherical equivalent of at least −0.5 diopters (D) in either eye) was higher in Singapore Malays (22.1%) than in Malays in Malaysia (9.2%; 95% confidence interval (CI) 11.2 to 14.7; p<0.001). Similarly, Singapore Chinese (40.1%) had higher prevalences than Malaysian Chinese (30.9%; 95% CI 1.5 to 16.9). Singapore Indians had a higher prevalence (34.1%) than Malaysian Indians (12.5%; 95% CI 17.4 to 25.9). The multivariate odds ratio of astigmatism (cylinder at least 0.75 D in either eye) in Singapore Malays compared with Malaysian Malays was 3.47 (95% CI 2.79 to 4.32). Ethnicity-specific hyperopia rates did not differ in Singapore and Malaysia. Conclusion: The ethnicity-specific prevalences of myopia in Singapore Malays, Chinese and Indians are higher than those in Malaysian Malays, Chinese and Indians. As Malays, Chinese and Indians in Malaysia have genetic make-up similar to that of Malays, Chinese and Indians in Singapore, environmental factors may contribute to the higher myopia rates.